OPTIMIZATION STRATEGY OF OVERSEAS OPERATION MANAGEMENT OF CHINESE ENTERPRISES BASED ON INTERNATIONAL EXECUTIVE EDUCATION COURSES - Wei, Yu; Waworuntu, Stephanus Remond (President University, 2024)
The purpose of this paper is to explore the challenges and optimization strategies faced by Chinese enterprises in their overseas operations and management processes. Jiangxi ZHENGBANG Plant Protection Co., Ltd, for example, conducts overseas operations mainly in Pakistan, Indonesia, Cambodia, Myanmar, Nigeria and 12 other countries. ZHENGBANG is a national high-tech enterprise focusing on the development, production and sales of pesticide dosage forms, pesticide intermediates and preparations, and is committed to the development of pesticide products for the prevention, elimination or control of agricultural and forestry pests and other pests, including insecticides, fungicides, herbicides and plant regulators. With the in-depth implementation of the